Estupro contra vulnerável: uma análise à luz dos princípios constitucionais e do sistema penal - Favoretto, Affonso Celso (2011)
The context of sexual crimes received important alterations by the Brazilian legislator, which materialized them through law 12.015/2009. The present paper turns around the interpretation of the mentioned transformation, specially focusing on the rape against vulnerable people, innovative penal type that since its advent, cause intense debate in Brazilian doctrine and jurisprudence. The task of interpreting the content of the crime in question only becomes possible because of the constitutional reading, being the penal constitutional principles and criminalization warrants, important tools of which the studious people and Penal Right operators have